USULAN PENINGKATAN KUALITAS PELAYANAN MENGGUNAKAN INTEGRASI IMPORTANCE PERFORMANCE ANALYSIS, KANO, DAN ANALISIS TRIZ DI KAFE NGOFFEE.ID - Yuniati, Yoanita; Prasetyo, Sigit (Teknik Industri Unikom, 2022)
Ngoffee.id is a cafe that is currently facing the problem of service quality. The problems that occur include slow order presentation, inadequate facilities in the parking lot, and health protocols that are not optimal. The research is aimed at producing a design for improving the quality of service. The research was conducted using the integration of the Importance Performance Analysis method with Kano and TRIZ analysis, to obtain quality improvement proposals. The results of distributing questionnaires to 100 respondents obtained an average satisfaction level of 3.15 and an importance level of 2.95 from a scale of 1 to 5. The TRIZ analysis obtained a quality improvement proposal, which consisted of the X13 attribute regarding the speed of cafe service in serving orders, the cafe can provide free snacks and drinks to customers, attribute X3 regarding the availability of adequate parking space with the suggestion that the cafe collaborates with other related to parking areas. Attribute X19 regarding the using masks, and attribute X21 regarding arranging seating positions, for both attributes the proposals generated are to provide masks and adjust seating positions according to health protocol. The proposal is expected to be able to improve the service quality of the Ngoffee.id cafe.